PENGARUH MEDIA TANAM DAN SISTEM FERTIGASI TERHADAP PERTUMBUHAN SERTA HASIL TANAMAN CABAI RAWIT (Capsicum frustescens L.) SECARA SEMI HIDROPONIK - Laela Nur Rohmah; Yacobus Sunaryo; Darnawi Darnawi (Universitas Sarjanawiyata Tamansiswa, 2018)
This research was conducted to determine the effect of types of planting media and kinds of fertigations on the results of cayenne pepper cultivated in semi-hydroponics. This research was carried out in the Greenhouse of the Faculty of Agriculture, University of Sarjanawiyata Tamansiswa.Â It has altitude of 112 m above sea level and temperature between 260 â€“ 280C. This research method was arranged in a Complete Randomized Block Design in Split Splot consisting of two treatment factors. The fisrt factor was the fertigation method as main factor consisted of 2 levels: spraying watering system and fertigation of the drip irrigation system. The second factor was the planting media as sub factor consisted 3 levels: rice husk charcoal + regosol soil (v/v= 1:1) ,rice husk charcoal + zeolite (v/v= 1:1), and rice husk charcoal.+ regosol + zeolite (v/v= 1:1:1). Each treatment unit used 3 sample plant. The results of the observations were analyzed using variance, followed by Duncan 's Multiple Range Test (DMRT) at the level of a = 5%. AThe results of the experiment indicated that there was an interaction beetwen planting media and kinds of fertigations for the variables observed in the number of flowers and fresh weight per plant. Where are, the treatment of planting media and the fertigation system had an effect on the yield of cayenne pepper, namely the fresh weight of fruit per plant. However, no interaction occurred beetwen planting media and kinds of fertigations of the variable observed in the plant height, number of leaves, number of fruits, fresh weight of the plants, dry weight of plants and fruit diameter. The best results of combinationâ€™s treatment rice husk charcoal+ regosol soil + zeolite(v/v= 1:1:1) with fertigation of the drip irrigation system indicated on fresh weight per plant